Financiamento externo e transiç\~ao energética nos países do BRICS - Maria Cândida Arrais de Miranda Mousinho; André Pires Batista Coelho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Despite the challenges for its development, the energy transition is crucial not only to achieve energy security and reduce energy dependence in politically unstable regions, but above all post- -pandemic to meet the goals established in the 2030 Agenda. In this context, countries considered developed have an essential role in the trajectory for a safe global energy transition and, Brazil, Russia, India, China and South Africa (BRICS) are also configured with unquestionable relevance: due to the economic, environmental and social representation they hold, these States are at the center of gravity of energy production and consumption. In that context, it is worth asking how the main global economies intersect with the countries that make up the BRICS regarding to financing for energy transition in these countries. Thus, the guiding question of this work is to know who are the main financiers of the countries that make up the BRICS for a low carbon economy within the scope of the OECD. The methodology adopted was based on the literature review that was combined with the data obtained in the prospection of the three databases chosen to carry out quantitative analyzes by summarizing statistical calculations. Among the results, it can be pointed out that among the BRICS, India was the country that received the most funding from OECD countries for energy transition and Germany was the main individual direct financier of the BRICS. It should be noted that, in relation to multilateral organizations, the World Bank played a leading role in financing the energy transition.
10419/284920
Keywords: F35; F64; Q42; Q56; 330; energy transition; financing; developed countries; BRICS